Inconsistencies in the Ḥanafī School's View of Children's Legal Competence - Fauzi, Moh.; Nurdin, Nazar (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2023)
This article examines the inconsistencies of the Ḥanafī school of thought regarding the legal capacity of children. The study of this issue is to prove whether or not there is harmony between the legal istinbat method (ushul fiqh) used and the legal product (fikih) created. In fiqh proposal it is determined that children do not have legal capacity so they are freed from all forms of legal imposition (taklif). The problem studied is the inconsistency of children's legal skills and arguments against this problem. This paper is based on qualitative data in the form of books on ushul fiqh and fiqh of thought from the Ḥanafī school of thought. Data is given meaning through verstehen, namely understanding by using a divergent, creative, and innovative mindset so that deeper meaning is found. After that, the data was analyzed using content analysis, namely taking inventory of data, simplifying it, and generalizing it. This is done interactively between the three components; data reduction, data presentation, and data verification. The results of the research show that there is an inconsistency in the Ḥanafī school of thought regarding legal competence. Inconsistency is seen in three ways; the standard has been and has not been the functioning of reason related to the age phases of the child, determining the impact of the benefits and harms contained in legal actions, and the scope of legal subjects. Thoughts on the legal skills of children other than the Ḥanafī school of thought which have not been studied in this paper need further research.